A Literature Synthesis and Evaluation of Experimental Studies in Agricultural Education Researches Within Period 2011-2021 (Universitas Negeri Semarang, 2022)
The purpose of this study is to find and synthesize existing Agricultural Education (AE) researches of Nigeria authors extraction that used experimental or quasi experimental designed and were published within period 2011-2021. A mixed approach research synthesis design was adopted. Five research questions were raised and answered. Thirty AE research articles met the selection criteria. The selected studies were synthesized based on research focus, recommendation, result, sample size and duration of treatment. Thirteen of the selected studies experimented on academic performance of students, out of which five shared themes with either of, method of active learning or technology. Five common themes in research recommendations were discovered by coding the recommendations of each publication, four of the selected studies recommend that government and school administrators should ensure adequate provision of technological devices in schools to make the use of technology effective in teaching. It was concluded that majority of the studies examined used a shorter treatment duration and that AE researches of Nigerian extraction were low. The impact of technology, academic achievement, and active learning approaches were trends in the synthesized studies. Professionals should be recruited and retrained to keep up with agricultural developmental trends, teachers should use video technology to enhance teaching and learning, and curriculum should be adjusted to include new innovative technique were among recommendations made.